Interface between Religion and Culture: A Critical Study of the Infiltration of Yoruba Tradition on the Practice of Title-Holding Among Egba Muslims of Ogun State, Nigeria (Global Journal of Human-Social Science, 2016)
Title-holding is an age long practice before the penetration of Islam in Egbaland, an area predominantly inhabited by the Yoruba speaking people of Ogun State, Nigeria. The acceptance of Islam by the Egbas reformed, to a large extent, the socio-religious and cultural lives of the people. The Yoruba traditional systems of marriage, naming and burial rites were, among others, influenced and reformed by Islam. However, a good number of the Egbas, like other Yoruba tribes which profess Islam, still retain some of their cultural beliefs and traditions. Consequently, there was an infiltration of Yoruba tradition and culture on certain Islamic practices and rites such as marriage, naming and funeral rites. Such infiltration can also be noticed in titleholding among the people. This paper, therefore, critically appraises the fusion of the Yoruba traditional elements to the Islamic practice of the title-holding among Egba Muslims. The paper adopts the historical approach establishing the institutionalization of titleholding in Islam. It then x-rays the practice of title-holding among the people. The paper then considers the similarities between the Muslim titles and the traditional titles patterned along the traditional set up among the four sections of the people.
Keywords: title -holding; Yoruba land; Egba Muslims; Egba land; Yoruba tradition